Memahami Sistem Self Service Menggunakan Unified Modeling Language - Lusi Ho; Syaiful Rahman; Abdul Munir (STMIK KHARISMA Makassar, 2021)
This study aims to determine whether by using the Unified Modeling Language application developers can easily understand the self service system. The method used in this study is the Unified Modeling Language method to produce system modeling in the form of three Unified Modeling Language diagrams (use case diagrams, activity diagrams, and class diagrams) and the test method to produce an average score of 89.75 test respondents' understanding. Based on the research results obtained, it is concluded that the use of the Unified Modeling Language makes it easier for application developers to understand the self service system of the Self Service in Food Menu and Order application so that it can be used as a benchmark if you want to develop Self Service in Food Menu and Order applications in the future.